Butterfly Customers: Strategies and Technology for Marketers - B. Srinivasa Rao, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Dynamics of customer engagement are hastily changing. Marketers must understand the entire customer journey and creatively apply the amicable strategies.  Digital era demands integrated strategies and integration of multidisciplinary strategies for greater customer engagement.   To continue acquiring, retaining, capturing transient   customer, marketers need to recognize this and innovate new strategies.  The present research aims at exploring the strategies to capture flit and retain Butterfly Customers.  The research is descriptive but exploratory in nature. The information collected from standard secondary sources and interviews/discussions with decision makers and experts in the domains of marketing, information technology and analytics. The results echo that capture flit and retaining Butterfly Customers is difficult but imperative to marketers.  The strategies and tools explored are useful to marketers to identify and capture flit and retain Butterfly customers. The study is exploratory hence there is a scope for experimental/empirical multidisciplinary research.
Keywords: Digital era; Butterfly Customers; Strategies to capture flit; ARM; TRMF Model; and Product Recommender System